Syukur: Perspektif Tafsir Al-Qur’an (Studi Komparasi Tafsir Al-Iklil dan Tafsir Al-Azhar) - Andaru Arimurti Kunta Wibisana; Ainur Rha’in (Departement of Mathematics Education, 2024)
There are problems with man's lack of awareness of gratitude for his achievements as a gift from Allah Almighty, selfishness and lack of awareness of success which is essentially a gift from Allah. Awareness of gratitude is considered very important as an expression of gratitude for the blessings given. Ironically, many are overfavored but lulled by egos and passions, causing discontent that encourages despicable acts such as corruption. The purpose of this article is to gain a comprehensive and in-depth understanding of the meaning of gratitude through the interpretation of the Qur'an. The research method applied is a qualitative approach by conducting a literature study analysis, this study compares between Tafsir al-Iklil Fi Ma'ani at-Tanzil by K.H. Misbah Mustafa and Tafsir al-Azhar by Buya Hamka. The results showed that gratitude is not just a verbal expression, but is reflected in actions. The interpretation of K.H. Misbah Mustofa emphasizes the improvement of worship and faith, while Buya Hamka focuses on the social aspect. In conclusion, gratitude is not only in the form of obedience to God, but is also reflected in social relationships. Thanking Allah is recognized as the key to additional favors, while dissatisfaction can lead to negative consequences such as istidraj or emptiness. This research provides comprehensive and in-depth insights into the meaning of gratitude, highlighting the importance of awareness of His blessings in achieving life success.